Gross recurrent laryngeal nerve invasion by extranodal extension in thyroid carcinoma - Xin Li; Xiang-yun Yao; Shi-rong Liu; Fang Mei; Bo Yu; Bing-yan Wang; Shi-bing Song; Shi Tan (BMC Cancer)
Abstract Background Lymphatic metastasis commonly occurs in patients with papillary thyroid carcinoma and medullary thyroid carcinoma. The clinical and imaging characteristics of recurrent laryngeal nerve (RLN) invasion by extranodal extension (ENE) of metastatic lymph nodes remain understudied. This study aimed to evaluate these characteristics in patients with thyroid carcinoma. Methods A retrospective cohort study was conducted on 77 patients treated between January 2012 and March 2024 with thyroid carcinoma demonstrating gross RLN invasion during surgery. Fifteen patients with gross RLN invasion by ENE of the metastatic lymph nodes were included. The primary endpoint was the percentage of preserved nerves. The secondary endpoints included vocal cord function and recurrence-free survival. Results Fourteen patients had papillary thyroid carcinoma (PTC), and one had medullary thyroid carcinoma (MTC). There was no case of distant metastasis in the series. In the PTC group, two patients presented with hoarseness. There were two (14.3%) cases of T1a, six (42.9%) cases of T1b, and nine (64.3%) cases with concomitant lateral lymph node metastasis. The stage of the MTC case was T3bN1a. Among all the cases included, ten (67.7%) and five (33.3%) right and left RLNs, respectively, were invaded by ENE of the central compartment lymph nodes. Ultrasonography showed lymph nodes wrapping beyond half of the circumference of the RLNs and indistinct boundaries between the nodes and RLNs. Seven patients (46.7%) had the tumor shaved off from the epineurium, and three (20.0%) had the integrity of the RLNs preserved with gross residual tumor. Permanent vocal cord paralysis occurred in two (13.3%) cases receiving neurectomy, of which one was of the PTC group, and the other one belonged to the MTC group. At the end of the follow-up period, two patients in the PTC group experienced locoregional recurrence. Conclusions Most patients with RLN invasion by ENE were asymptomatic. Sonography is feasible for assessing the location of metastatic lymph nodes in relation to the RLN in this preliminary study. Careful central compartment evaluation for patients with lymphatic metastases from thyroid carcinoma is conducive to nerve preservation and radical resection of lesions, especially for patients with MTC.